Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0024459
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid State of Proteins in Human Disease

Abstract: Over 30 human amyloidoses, such as prion disease, Alzheimer's disease and Parkinson's disease, are characterised with the formation of amyloid plagues. Amyloid plagues are the products of protein aggregation, which begins with soluble amyloidogenic proteins into insoluble amyloid fibrils. Mounting evidences suggest that those aggregation processes are noxious to cells, during which the formation of oligomers is believed to be the most toxic species. In vivo , it has been proven that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The amyloid fibril refers to an insoluble supramolecular structure with a high aspect ratio and ordered characteristics generated by protein self-assembly. 1 The formation of amyloid fibers has been implicated in many neurological diseases, such as Parkinson's, Alzheimer's, Creutzfeldt−Jakob disease, type II diabetes, and bovine spongiform encephalopathy, 2 making the study of the mechanism and conditions of protein selfassembly very interesting. Recently, it was found that many food proteins, such as β-lactoglobulin (β-lg), 3 zein, 4 and soy protein, 5 can also self-assemble into amyloid fibers under certain conditions and even form protein fibers of different sizes and shapes by controlling the temperature, pH, solvent polarity, ionic strength, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The amyloid fibril refers to an insoluble supramolecular structure with a high aspect ratio and ordered characteristics generated by protein self-assembly. 1 The formation of amyloid fibers has been implicated in many neurological diseases, such as Parkinson's, Alzheimer's, Creutzfeldt−Jakob disease, type II diabetes, and bovine spongiform encephalopathy, 2 making the study of the mechanism and conditions of protein selfassembly very interesting. Recently, it was found that many food proteins, such as β-lactoglobulin (β-lg), 3 zein, 4 and soy protein, 5 can also self-assemble into amyloid fibers under certain conditions and even form protein fibers of different sizes and shapes by controlling the temperature, pH, solvent polarity, ionic strength, etc.…”
Section: ■ Introductionmentioning
confidence: 99%